A Mechano-Chemical Computational model of Deep Vein Thrombosis - Jimoh-Taiwo, Qudus Boluwatife (Department of Mechanical Engineering, 2022)
Deep Vein Thrombosis (DVT) is the formation of a blood clot in a vein, usually in the body's lower extremities. If untreated, DVT can lead to pulmonary embolism (PE), heart attack and/or stroke, which can be fatal. According to literature, DVT affects 0.2% of people in developed countries and about 0.3%-1% in developing countries. In the past, various computational models of DVT were developed. Most models account for either the mechanical factors or biochemical factors involved with DVT. Developing a model that accounts for both factors will improve our understanding of the coagulation process. This study developed a three-dimensional DVT computational model in idealized and realistic common femoral vein (CFV) geometries. The model considers the biochemical reactions between thrombin and fibrinogen, pulsatile blood flow, and clot growth within the vessel. The model was validated using a simplified experimental setup with flow, thrombin, and fibrinogen. Computational fluid dynamics (CFD) simulations were carried out using the ANSYS modelling suite. The Navier-Stokes equations were solved to determine the fluid flow. Based on a clinical dataset of pulsatile blood flow, the laminar flow of blood with a Poiseuille velocity profile was applied at the inlet. Darcy's law was used to account for porosity changes in the clot, with the clot represented by zones with lower porosities. The transport equations were used for changes in the concentration of the biochemical protein species. Thrombin was released into the bloodstream from an injury zone on the wall of the vein. The Michaelis-Menten equation was used to represent the conversion of thrombin and fibrinogen to fibrin, the final product of the coagulation process. The computational model solves the blood flow pattern proximally, locally, and distally to clot formation at the injury zone. The model also predicts the size of the clot and the rate of clot growth. The model was first developed in a two-dimensional geometry. This model was used to investigate clot formation under different cases comparing how introducing thrombin as a flux value differs from specifying it as a fixed concentration. It was confirmed that to apply the flux condition, the thrombin concentration needs to be divided by a factor derived by multiplying the area of the injury zone and the time step size. The same model was then used to conduct a parametric study to determine the effects of varying parameters such as inlet velocity, vein diameter, and peak thrombin concentration on the size and shape of clot formed. Peak thrombin concentration was the key factor driving the initiation and propagation of clot in the vein. The model was then extended to an idealized three-dimensional geometry. This computational model was validated using results from an experimental clot growth study. The experiment comprised a steady flow of fibrinogen in a cylindrical pipe, with an injection of thrombin into the flow at the injury site, resulting in fibrin formation. A qualitative comparison was then made between the experimental clot and the clot formed in silico. Although quantitative measurements were not made, there were similarities in the shapes and sizes of the clots. The validated computational model was used to compare clot formation under steady and pulsatile flow conditions. Realistic clot growth was observed and compared to the steady flow condition. It was found that a larger clot formed under pulsatile conditions. Clot formation with the presence of valve activity was also investigated. The effect of opening and closing of the valves was achieved by varying the blood flow diameter at the inlet instead of modelling the valves as solid walls and accounting for the leaflet movement by solving the governing equations for the fluid-solid interaction (FSI), as used in existing models. The model was then applied to a patient-specific geometry. Realistic clot growth was achieved using this model, and the clot was compared to a clot formed in vivo, as depicted in the original imaging scan. The model helps us better understand the clot growth process in the femoral vein on a patient-specific level. It also shows that the presence of venous valves increases the size of clot formed compared to steady flow. However, the high strain rate present makes the clot formed smaller than in standard pulsatile flow cases.